Heaven official's blessing = Tian guan ci fu. 2 - Moxiangtongxiu (Danmei (Seven Seas Entertainment), 2022)
"Xie Lian has confirmed that the bewitching youth San Lang is actually Hua Cheng, one of the Four Calamities and a supreme ghost despised by all heavenly officials. Still, he has trouble matching the terror of his companion's reputation with the charming, clever, and protective young man he's come to know. When a distress signal leads Xie Lian into Ghost City, a bustling metropolis containing all the horrors and delights of the dead, he sees Hua Cheng in his element--and his true form--for the first time. But despite their chemistry and care for one another, there are missions to fulfill and secrets to uncover, and Xie Lian's centuries of troubled history are never far behind."--